Rhetoric, Materiality and Practice of Historical Knowledge in Colombia during the Second Half of the 19th Century (2014)
Rhetoric, as a technique responsible for the intelligibility of speech, for enunciation modes and spaces, for purposes and audiences, defined until the 19th century the existence of the so-called “literary genres turned into history, literature and journa